Sakramentalia zastrzeżone duszpasterzom w XVII–XVIII w. (na przykładzie archidiecezji gnieźnieńskiej) - Zabraniak, Sławomir (Limes. Studia i materiały z dziejów Europy Środkowo-Wschodniej (czasopismo archiwalne), 2021)
Following the Council of Trent, the Church in Poland used Roman liturgical books with minor adaptations to accommodate Polish traditions. The Piotrków Ritual (1631) – Polish edition of the Roman Ritual – describes several dozen different sacramental rites. Sacramentals have constituted an important part of religious life. And many of those were reserved for parish priests.